A CLINICAL STUDY TO EVALUATE THE EFFICACY OF SELECTED TREATMENT MODALITY IN THE MANAGEMENT OF VATA KANTAKA - MPN, Pramodani; WJ, Wickramarachchi (International Journal of Research -GRANTHAALAYAH, 2017)
Walking in irregular or uneven ground, Structural deformity of foot, Excessive strain on heels etc lead to vitiation of Vata dosha. Aggravated Vata is lodged in ankle joint, especially in dependent parts like heel and hence the pain is caused due to reduced strength of muscles and joints. ‘Kantaka’ refers to thorn. The pricking pain felt due to vitiated Vata is termed as Vata kantaka. This condition is usually seen in the case with calcaneus spur. Symptoms are Pain in heel and surrounding region. Pain is more evident soon after waking up in the morning and if the patient stands up, After a long rest and Increase in heel pain on standing for long time, running and walking. According to previous researches Planter heel pain is the most prevalent complaint to presenting foot and ankle specialists and may be seen in upwards of 11 % to 15% of adults. So it is the need of hour to focus effective practices which yields good results. In the present study thirty patients were selected and treated with Pinda Thaila Abyanga, Rasnadi sweda followed by application of Hinguadi lepa mentioned in Traditional medicine in Sri Lanka, daily for one month. The assessment was carried out on the basis of relief found in the cardinal signs and symptoms of the disease adopting scoring, depending upon their severity. Significant reduction in pain was seen at the end of the study with P value of < 0.05. Also there was reduction in other symptoms such as cracks, pruritus, burning sensation and laxity of skin over the foot .There were no adverse effects reported during the study. Therefore it can be concluded that the selected treatment modality is beneficial in managing Vata kantaka.